The Rules of Radical Microsiology - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2005)
Contrary to the popular definition of qualitative research as “the new mode” of cognition we can see qualitative methods as having at its essence the concepts of hermeneutics, pragmatism, and radical microsociology. The focus of this article is on the historical roots of qualitative method and the methodological tension created by the foundational and discoursive terminology. The goal of this paper is to discuss and suggest a need for sociology to more thoroughly integrate microsociological insights into its theory and practice. It is from this point of view that we must consider the contemporary “demise” of empiricism and make explicit some substantive connections between the new ways of cognition, i. e. qualitative methods, “post-“ insights, and “radical” microsociological trends. Within the larger context of sociology as an academic discipline, a growing breach now exist between the proponents of a so-called quantitative epistemology and those who have identified themselves as qualitative researchers. The transformation of recent methodology has been accompanied by a proliferation of qualitative techniques of research. Its focus shifts from foundational attempts to the discoursive, contextual, and indexical problems. Supposing that the two ways of cognition are based on different sociological traditions and methodological justifications leads to asking the question posed to us by the dualist context of latter-day sociological inquiry: what are the roots of qualitative research? This paper begins by arguing that progress towards a fully articulated sociological practice must proceed now from a historically focused analysis of different methodological ideas. The themes and the principles of the classic methodological works of these traditions reveal the plausibility of the claim that the incorporation of their content is central for recent methodology. The main argument of this article is that the highlighting and criticizing particular arguments relevant to the debate between the quantitative sociologists and the critics of quantitative researches leads to a better understanding of the radical transformation of the contemporary critical sociological thought. From the critical point of view the main task is to ensure the proceeding potency to make sociological discourse negotiable.